The normative defense of free market capitalism : did the free market cause the financial fiasco? - Machan, Tibor R. (Addleton Academic Pub., 2011)
Machan's book advances an indispensable normative case for the free market system of economy. He addresses the different approaches taken to showing the superiority of the system to others and also discusses the charge that the recent financial fiasco was ...